Research priorities for improving cognitive and neuropsychological outcomes in hydrocephalus - Nickolas Dasher; T. Andrew Zabel; Maria Garcia-Bonilla; Lauren L. Jantzie; Mark G. Hamilton; Michael A. Williams; Monica J. Chau (Fluids and Barriers of the CNS)
Abstract Hydrocephalus is a neurological disorder that impacts approximately 85 per 100,000 individuals worldwide and is associated with motor and cognitive impairments. While many advances in surgical interventions have helped substantially improve the survival rates and quality of life of those affected, there continues to be significant gaps in our understanding of the etiology of this heterogeneous condition as well as its specific neuropsychological and functional challenges across different phases of life. To address these limitations, the Hydrocephalus Association and Rudi Schulte Research Institute organized a workshop titled, “Improving Cognitive and Psychological Outcomes in Hydrocephalus”, composed of top academics in the fields of hydrocephalus, cognition, and neuropsychology, as well as individuals with hydrocephalus or their caregivers. The purpose was to review the available evidence and propose pertinent areas of further research to improve the cognitive functioning, functional status, and quality of life of individuals with hydrocephalus. These topics included cognitive and neuropsychological assessments and daily-life function of children and adults living with hydrocephalus, biomarkers of cognitive function, animal modeling of hydrocephalus, and the longitudinal impact of hydrocephalus treatment. The following paper outlines four primary areas that warrant research: (1) neuropsychological phenotypes, (2) treatment-focused research considerations, (3) translational pre-clinical tools, and (4) establishing pathways for longitudinal care. Through the efforts of this group, the goal of this manuscript is to inspire and direct scientific and clinical inquiry towards these noted research priorities to further improve the lives of individuals with hydrocephalus and their families.